Combined pelvic floor training and hormonal therapy for endometriosis pain recurrence: a propensity score-matched study - Jie Song; Hui Dong; Zhen Chen (Frontiers in Medicine, 2026)
Background Endometriosis (EMS) causes debilitating pain and reduces quality of life. Whether pelvic floor muscle training (PFMT) provides independent, additive benefits beyond standard postoperative hormonal suppression remains unknown. Methods A retrospective cohort study was conducted on 446 women with surgically confirmed EMS between June 2022 and May 2024. Patients were categorized into five groups: PFMT-only ( n = 98), PFMT+long-term adjuvant progestogen (PFMT+LAP; n = 91), PFMT+combined oral contraceptives (PFMT+COC; n = 87), LAP-only ( n = 85), and COC-only ( n = 85). Propensity score matching (PSM) with 28 baseline covariates was applied to isolate the effects of PFMT. Primary outcomes included 12-month pain recurrence, health-related quality of life (EHP-30), and recurrence-free survival. Results After PSM, 12-month dysmenorrhea recurrence was significantly lower in combination groups compared to hormonal therapy alone: PFMT+LAP vs. LAP-only (36.5% vs. 75.0%; OR = 0.192; p = 0.0002) and PFMT+COC vs. COC-only (38.3% vs. 68.1%; OR = 0.291; p = 0.0072). Multivariable logistic regression confirmed PFMT as an independent protective factor against recurrence for dysmenorrhea, chronic pelvic pain, and dyspareunia (all p<0.005). No significant difference was found between LAP-only and COC-only groups (OR = 1.04; p = 0.914), indicating PFMT drove the incremental benefit. Linear mixed-effects modeling showed a significant time-group interaction for EHP-30 pain scores ( F = 39.14; p<0.001). Kaplan-Meier analysis demonstrated superior recurrence-free survival for combination regimens (log-rank p<0.001). Conclusion Pelvic floor muscle training combined with hormonal therapy significantly reduces pain recurrence and quality-of-life burden while extending recurrence-free survival compared to hormonal therapy alone. These findings suggest that PFMT may confer a clinically meaningful adjunctive benefit. However, given the retrospective, non-randomized design of this study, confirmation in prospective randomized controlled trials is warranted before routine integration into postoperative endometriosis management protocols can be recommended.